A cadaveric study of anatomical variation of sphenoparietal sinus and superficial sylvian draining veins - Arumugam, Ananda; Nagalingam, Harvinth; Jessie, Hiu; Cheah, Pike-See; Abdelwahab, Emad M. (Edizioni Minerva Medica, 2024)
BACKGROUND: The sphenoparietal sinus (SPS) is a dural venous sinus. It was coined and gained interest in 19th century. However, controversies exist in the drainage of superficial sylvian veins (SSV). One of the key steps in the trans-sylvian and subtemporal approach is to identify SPS and bridging veins from SSV to create a wide surgical corridor. Hence, the aim of this study was to delineate the microsurgical anatomy and variation of the sylvian draining veins. METHODS: Thirty fresh cadavers were examined in Forensic Department, Queen Elizabeth Hospital between October 2020 to October 2021 and were anatomically analyzed. The cadaveric data collected through a data collection sheet were analyzed using SPSS version 22.0 (IBM Corp., Armonk, NY, USA). RESULTS: The studied cadavers were 76.7% male and 23.3% female with a median age of 52.5 years old. All cadavers had SPS on both sides and drain to the ipsilateral cavernous sinus. The number of SSV drainage (SSVD) varied from 0 to 4 veins on both hemispheres. About 40% of cadavers had three veins on the left hemisphere, 36.7% had two and three veins on the right hemisphere, and 3.3% had no draining veins on either side. Based on cadaveric data, a new classification for the SSVD-SPS was formulated to describe the number (from 4 to 0) of SSVD veins: Type A to type E. CONCLUSIONS: We have consolidated our hypothesis on the presence of SPS and variance in the number of draining veins to SPS. This new classification provides a new microsurgical nomenclature that facilitates future use in neuroanatomy and neurosurgery.